New records and noteworthy data of plants, algae and fungi in SE Europe and adjacent regions, 19 - Marko S. Sabovljević; Gordana Tomović; Sorin Ștefănuţ; Vladan Djordjević; Sara Stanković; Sanja Z. Djurović; Božo Frajman; Petya Boycheva; Mariya Kaschieva; Péter Szűcs; Aneta D. Sabovljević; Ivana Trbojević; et al. (Botanica Serbica)
This paper presents new records and noteworthy data on the following taxa in SE Europe and adjacent regions: mycorrhizal fungus Russula sapinea, parasitic fungus Podosphaera polemonii, saprotrophic fungi Ophiognomonia melanostyla and Plagiostoma apiculatum, diatom alga Nitzschia reskoi, stonewort Nitellopsis obtusa, liverwort Mannia triandra, mosses Buxbaumia viridis and Leptodon smithii, monocots Epipactis purpurata and Orchis × beyrichii and dicots Euphorbia orjeni, Fallopia × bohemica, Nuphar lutea and Saxifraga pedemontana subsp. cymosa.